The Potential of Carbon Border Adjustments to Foster Climate Cooperation - Timothé Beaufils; Joschka Wanner; Leonie Wenz (CESifo GmbH, 2024)
The European Union (EU) is implementing a Carbon Border Adjustment Mechanism (CBAM) at its borders, which will require exporters of basic materials to surrender emission permits when exporting to the EU market. Since it makes foreign producers compete under a carbon price, the EU CBAM may motivate some trade partners to implement their own carbon pricing mechanisms, thereby encouraging the creation of a coalition of countries with ambitious carbon pricing policies protected by a joint CBAM. Such geostrategic potential of the EU CBAM has been identified in previous literature, but the conditions under which it could be realised remain largely unknown. Here, we present a modelling framework to simulate the potential of CBAMs to motivate the creation of climate coalitions. We use a fully interlinked New Quantitative Trade model to evaluate the pay-offs of a dynamic club negotiation model. Compared to previous research, our approach allows for a more granular definition of climate policies and requires relatively little input data and numerical power. This allows us to explore the formation and stability of climate coalitions under a broader range of CBAM implementation options. Our results highlight that the potential of a CBAM-based climate coalition strongly depends on the exact CBAM design. In its current version, the EU CBAM would only trigger the formation of a modest coalition. Future extensions of the EU CBAM could motivate the adoption of carbon pricing in all countries except China, India and Russia. Meanwhile, export rebates shrink its coalition-building potential.
Keywords: C68; F18; Q56; 330; Carbon Border Adjustment; climate policy; international trade; climate cooperation; climate clubs